Diagnostics of soil formation and weathering processes based on the content of alkaline and alkaline earth macroelements in soils of the Middle Urals (Basegi Ridge) - I.A. Samofalova (Учёные записки Казанского университета: Серия Естественные науки)
In this paper, the geochemical indicators based on the concentrations of alkaline and alkaline earth macroelements (K, Na, Ca, Mg), as well as aluminum and silicon, were studied for the territory of the Basegi Ridge on the western slope of the Middle Urals. The basin of the Malyi Baseg River on the Northern Baseg Mountain was singled out as a key site. The bulk composition of all elements was measured with the help of X-ray fluorescence. The calculations of the indices given above show that the concentrations of alkaline and alkaline earth metals are higher in the soils of the mountain-forest belt, while K2O and MgO are dominant in the soils of the golets-subgolets belt. K2O was found to be evenly distributed in all soils and had a relatively stable concentration. The data obtained revealed that the differentiation of the soil profile by chemical composition depends on the content of K2O and MgO, which is a sign of brown soil formation. The following geochemical indicators were measured to register the processes of physical and chemical weathering and soil formation: total bulk concentration of Mg + Ca + K (%); CaO/MgO molecular ratio; normalized alkalinity modulus; alumina index; alkaline modulus; plagioclase index of alteration; weathering intensity. Using the calculated bulk concentrations of alkaline and alkaline earth macroelements and the data on chemical heterogeneity of the soil cover in the high-altitude landscapes of the Middle Urals, the evolutionary and genetic features of the soils under consideration were identified.